Identifikasi Kesalahan Mahasiswa Pendidikan Matematika dalam Menyelesaikan Soal Materi Grup di Universitas Negeri Medan - Khafifah F, Siti; Novita Sari Maria Br Manullang; Sri Lestari Manurung; Azra Khumairah; Iren Dwi Adinda Sitepu (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Difficulties in understanding Algebraic Structures, particularly group theory, pose challenges for Mathematics Education students. This study aims to identify and analyze the types of errors students make in solving group-related problems at Universitas Negeri Medan. This research employs a qualitative descriptive method, involving 35 students who have taken the Algebraic Structures course as research subjects. Data were collected through a written test consisting of three questions related to binary operations and groups. The results indicate that students make three main types of errors: conceptual, procedural, and technical errors. Conceptual errors arise due to a lack of understanding of group properties, procedural errors result from inaccuracies in following problem-solving steps, and technical errors occur due to mistakes in calculations and mathematical symbol manipulations. The findings of this study are expected to provide insights for lecturers in designing more effective teaching strategies, such as implementing visualization-based learning methods and interactive discussions to enhance students' comprehension of Algebraic Structures.